1990
DOI: 10.1111/j.1365-2621.1990.tb05196.x
|View full text |Cite
|
Sign up to set email alerts
|

Meat By‐product Protein Composition and Functional Properties in Model Systems

Abstract: Composition and functional properties of selected meat by-products were studied. Mechanicallv deboned chicken meat (MDCM) and meat by-products (pork lung lodes, pork liver, beef lung lobes, bdef spleen, beef heart) varied in their proximate composition, amount of the three major protein fractions [low ionic strength soluble (LIS), high ionic strength soluble (HIS), insoluble] and collagen content. Cooked batter mode1 system reheat yield was positively correlated with the quantity of HIS proteins and the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 19 publications
1
40
1
1
Order By: Relevance
“…Results previously provided for sausages manufactured with various mixtures of surimi and chicken breast meat and commercial MDCM showed that breaking force was significantly higher in the formulations containing surimi-like material instead of chicken meat (Jin et al, 2008) and that increasing the levels of surimi in combination with added fat increased shear force values, and that increasing the levels of surimi in combination with added water increased shear force in pasteurized pork-surimi sausage systems (Murphy et al, 2004). Nuckles, Smith, and Merkel (1990) reported that frankfurter made from mixtures of beef heart extract and MDCM are necessary to produce the desired bind in frankfurter formulations due to the high ionic strength of soluble proteins.…”
Section: Texture Analysismentioning
confidence: 89%
“…Results previously provided for sausages manufactured with various mixtures of surimi and chicken breast meat and commercial MDCM showed that breaking force was significantly higher in the formulations containing surimi-like material instead of chicken meat (Jin et al, 2008) and that increasing the levels of surimi in combination with added fat increased shear force values, and that increasing the levels of surimi in combination with added water increased shear force in pasteurized pork-surimi sausage systems (Murphy et al, 2004). Nuckles, Smith, and Merkel (1990) reported that frankfurter made from mixtures of beef heart extract and MDCM are necessary to produce the desired bind in frankfurter formulations due to the high ionic strength of soluble proteins.…”
Section: Texture Analysismentioning
confidence: 89%
“…In addition to pH and total protein level, the types of proteins and their solubility in high ionic strength can affect the EC. Liver has a lower collagen content than heart, spleen and lung (Nuckles et al. 1990).…”
Section: Resultsmentioning
confidence: 99%
“…1990). However, liver has a high content of soluble proteins, particularly low ionic strength soluble (LIS) proteins (Nuckles et al. 1990; Devatkal et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations